NILAI SOSIAL PADA NOVEL PADANG BULAN KARYA ANDREA HIRATA (KAJIAN SOSIOLOGI SASTRA) - Afrianus Lapu; Indayani Indayani (Universitas PGRI Adi Buana Surabaya, 2018)
The selection of this novel as an object of research is based on a thought that the novel is lifted from human life to fight for its life, amidst the dynamics of social life, patience, laughter, devout worshipers, diligently working and learning, Shortcuts of love, caring. This study aims to describe the social values ​​contained in the novel